1999
DOI: 10.1128/iai.67.1.342-349.1999
|View full text |Cite
|
Sign up to set email alerts
|

Partial Protection againstPlasmodium vivaxBlood-Stage Infection inSaimiriMonkeys by Immunization with a Recombinant C-Terminal Fragment of Merozoite Surface Protein 1 in Block Copolymer Adjuvant

Abstract: Merozoite surface protein 1 is a candidate for blood-stage vaccines against malaria parasites. We report here an immunization study ofSaimiri monkeys with a yeast-expressed recombinant protein containing the C terminus of Plasmodium vivax merozoite surface protein 1 and two T-helper epitopes of tetanus toxin (yP2P30Pv20019), formulated in aluminum hydroxide (alum) and block copolymer P1005. Monkeys immunized three times with yP2P30Pv20019 in block copolymer P1005 had significantly higher prechallenge titers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
89
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(94 citation statements)
references
References 46 publications
(46 reference statements)
4
89
0
1
Order By: Relevance
“…In addition, several studies on naturally acquired immunity showed that the antibodies (IgG1 and IgG3) against this antigen are correlated with protection (20)(21)(22)(23). Moreover, among residents of West African countries, the presence of anti-PfMSP-1 19 -specific antibodies correlated with resistance to the disease (20,22) and purified MSP-1 19 -specific IgG from human sera inhibited erythrocytic invasion in vitro (24).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, several studies on naturally acquired immunity showed that the antibodies (IgG1 and IgG3) against this antigen are correlated with protection (20)(21)(22)(23). Moreover, among residents of West African countries, the presence of anti-PfMSP-1 19 -specific antibodies correlated with resistance to the disease (20,22) and purified MSP-1 19 -specific IgG from human sera inhibited erythrocytic invasion in vitro (24).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, numerous studies have been conducted to evaluate the efficacy of the merozoite surface protein-1 (MSP-1) (3-10) as one of the most important blood-stage vaccine candidates that is present on the surface of all known Plasmodium spp., including P. vivax (PvMSP-1) and P. falciparum (PfMSP-1). Antibody to the C-terminal region of this protein (MSP-1 19 ) has been shown to block parasite invasion in vitro (11)(12)(13). Earlier studies have demonstrated that immune responses elicited separately by PvMSP-1 19 (14,15) or PfMSP-1 19 (16)(17)(18) antigens in mice induced high levels of IgG1 antibodies followed by IgG2a and IgG2b as well as a high level of IFN-c. A partial protection was also observed after immunization of nonhuman primates with PfMSP-1 19 (5) and PvMSP-1 19 (19).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations